2018
DOI: 10.5902/1980509831586
|View full text |Cite
|
Sign up to set email alerts
|

EXIGÊNCIAS NUTRICIONAIS DE MUDAS DE<i> Dipteryx alata</i> SOB LIMITAÇÃO NUTRICIONAL

Abstract: RESUMOObjetivou-se, neste estudo, avaliar os requerimentos nutricionais e o efeito da limitação de nutrientes no desenvolvimento de mudas de baru (Dipteryx alata Vogel) utilizando a técnica da limitação nutricional. O ensaio foi estabelecido em delineamento inteiramente casualizado com 12 tratamentos e oito repetições. Os tratamentos adotados foram os seguintes: completo 1 (C1 -adubado com N, P, K, S, B, Cu, Zn e calagem), completo 2 (C2 -adubado com N, P, K, S, Ca, Mg, B, Cu, Zn, sem calagem), tratamentos com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 9 publications
3
10
2
2
Order By: Relevance
“…Tamarind (Tamarindus indica L.) seedlings fertilized with P (10,000 mg P 2 O 5 dm -3 substrate), when N is applied (800 mg dm -3 substrate) showed higher growth, and the combined application of both nutrients is recommended to obtain the largest average length of seedlings of this species (SOUZA et al, 2007). In another study, nitrogen and phosphorus were the nutrients that most affected the growth of barueiro seedlings under nutritional limitations, demonstrating their importance for plant development (SOUSA et al, 2018).…”
Section: Resultsmentioning
confidence: 94%
“…Tamarind (Tamarindus indica L.) seedlings fertilized with P (10,000 mg P 2 O 5 dm -3 substrate), when N is applied (800 mg dm -3 substrate) showed higher growth, and the combined application of both nutrients is recommended to obtain the largest average length of seedlings of this species (SOUZA et al, 2007). In another study, nitrogen and phosphorus were the nutrients that most affected the growth of barueiro seedlings under nutritional limitations, demonstrating their importance for plant development (SOUSA et al, 2018).…”
Section: Resultsmentioning
confidence: 94%
“…Boni et al (2016) reported N content values in baru seedlings of 26.4 g per kg, which falls within this range. While evaluating Baru's nutritional status, Souza et al (2018) found that suitable N levels for seedling development ranged from 20.20 to 26.00 g per kg.…”
Section: Resultsmentioning
confidence: 99%
“…A study with Dioscorea alata L. addressed the specific requirement of P and N (nitrogen) for biomass accumulation (SOUSA et al, 2018), with increasing linear QDI responses to different P doses, especially when accompanied by nitrogen fertilization (PINHO et al, 2019). Research shows that inoculation with AMF improve the uptake and ratio of N and P in plants, directly influencing their growth (AUGÉ et al, 2016;KANDHASAMY et al, 2020).…”
Section: Figurementioning
confidence: 99%